Restoration of South African estuaries: successes, failures and the way forward. Issue 1 (2nd January 2023) - Claassens, L; Adams, JB; de Villiers, NM; Wasserman, J; Whitfield, AK
Abstract : Major threats to South African estuaries include freshwater flow alterations, urbanisation, habitat transformation, deteriorating water quality, increased biological invasions and resource over-exploitation. Although South African estuary restoration is in its infancy, important lessons have been learnt through past efforts undertaken in some of the most impacted systems. This review presents case studies focused on hydrological and physical restoration actions, while recognizing the need to implement urgent remedial measures to restore the populations of targeted estuary-associated marine fish species. Common interventions designed to arrest declining estuary health include artificial management of estuary mouths and the use of artificial structures to restore tidal action and remediate erosion damage. Limited natural habitat restoration actions have been conducted on the subcontinent. Fortunately, estuaries are resilient ecosystems and can recover fairly rapidly if appropriate restoration interventions are successfully applied. Restoration needs to be co-ordinated through a national strategy which is currently not in place. It is particularly important to address the root cause of deterioration through active restoration and/or rehabilitation measures rather than only managing symptoms. The implementation of existing and future conservation legislation regarding the exploitation of natural resources within estuaries needs to be prioritised, so that over-exploited angling and subsistence fish species populations can recover.